2009
DOI: 10.1186/1745-6215-10-88
|View full text |Cite
|
Sign up to set email alerts
|

The Irish DAFNE Study Protocol: A cluster randomised trial of group versus individual follow-up after structured education for Type 1 diabetes

Abstract: Background: Structured education programmes for individuals with Type 1 diabetes have become a recognised means of delivering the knowledge and skills necessary for optimal self-management of the condition. The Dose Adjustment for Normal Eating (DAFNE) programme has been shown to improve biomedical (HbA 1c and rates of severe hypoglycaemia) and psychosocial outcomes for up to 12 months following course delivery. The optimal way to support DAFNE graduates and maintain the benefits of the programme has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…The DSQOLS was designed to evaluate the Düsseldorf STTP, on which DAFNE is based. Psychometric validation of the scale in English used data from this study and two others (10,11) and will be reported elsewhere. The DSQOLS includes 57 items that form six subscales summed to gain a total score.…”
Section: Methodsmentioning
confidence: 99%
“…The DSQOLS was designed to evaluate the Düsseldorf STTP, on which DAFNE is based. Psychometric validation of the scale in English used data from this study and two others (10,11) and will be reported elsewhere. The DSQOLS includes 57 items that form six subscales summed to gain a total score.…”
Section: Methodsmentioning
confidence: 99%
“…Detail of the study methodology for the Irish DAFNE Study has been published elsewhere 11 . Briefly, six outpatient hospital diabetes clinics delivering the DAFNE programme on the island of Ireland participated.…”
Section: Methodsmentioning
confidence: 99%
“…This larger study is a cluster RCT evaluating the impact of two different methods of follow-up of DAFNE graduates on biomedical and psychosocial outcomes [5]. …”
Section: Methodsmentioning
confidence: 99%